Infrared thermography for risk reduction of nosocomial cross infections during the COVID-19 Pandemic - Castro, Renata Rodrigues Teixeira (2021)
Introduction: Among millions of people who may be infected with COVID-19, patients with cardiovascular and oncologic diseases exhibit the highest risks of having worse outcomes. These patients are subject to chronic disease decompensation and may be subjected to cross-infection while visiting health facilities that are taking care of COVID-19 infected patients. Objective: To present scientific evidence and propose the use of infrared thermography for the reduction of viral cross-infection in healthcare facilities. Methods: Theoretical essay Results: Previous experience in pandemic show favorable results with the use of infrared thermography identifying infected patients and reducing the possibility of cross infections. Conclusion: Infrared thermography is a radiation-free, relatively inexpensive, noncontact, and noninvasive technology that could be used for mass-screening of patients and visitors with fever, especially in services where patients with cardiovascular disease seek for medical care, reducing the risk of cross-infection.